The magnitude of sagittal head posture displacement and patient demographics predict rehabilitation outcomes in patients with chronic nonspecific neck pain - Ghydaa Anwar; Ibrahim M. Moustafa; Amal Ahbouch; Abdulla Alrahoomi; Deed E. Harrison (Scientific Reports)
Abstract A multicenter, prospective consecutive case series study was conducted in 5 physiotherapy clinics in the UAE from January 2021 to March 2023 to assess rotations and translations of head posture parameters as potential predictors of conservative therapy outcomes in patients with chronic non-specific neck pain (CNSNP). Eighty-six patients (mean age 35 yrs., 65% male) with CNSNP underwent conservative therapy. All participants received a detailed examination including a computerized cervical spine posture analysis and demographic data was collected. Interventions included specific exercises, diathermy, longitudinal traction, education, a detailed exercise program, ergonomic advice, and medications. Interventions were applied 3 times per week for 8 weeks. Follow-up was 6-months after final treatment. A successful outcome was based on a minimum improvement of the following four outcomes using the patient centered outcome questionnaire (PCOQ): (1) reduction of pain by 17.5 points (0–100 NRS); (2) fatigue reduction by 7.5 points; (3) distress reduction by 5 points; and (4) interference reduction by 9.5 points. At 6-month follow-up it was found that success rates for pain, fatigue, distress, and interference were above 60% for the total participants. The logistic regression for predicting overall success in combined outcomes based on age, gender, smoking status, marital status, and sagittal head translation was: (1) Age: the odds ratio (0.69) suggests that as age increases, the likelihood of overall success decreases (p = 0.001); (2) Sex: females have higher odds of overall success compared to males (OR = 2.71, p < 0.001); (3) Smoking status and marital status: neither of these factors were statistically significant predictors of overall success; (4) Sagittal head translation: each unit increase (more anterior) in this abnormal posture reduced the odds of success by 13%, showing a strong and significant effect (OR = 0.13, p < 0.001). Overall, our findings indicate that younger age, female sex, and less sagittal head translation all had a statistically significant impact on the likelihood of success of 6-month outcomes in patients suffering CNSNP.